2023
DOI: 10.2147/jir.s391932
|View full text |Cite
|
Sign up to set email alerts
|

Fashionable, but What is Their Real Clinical Usefulness? NLR, LMR, and PLR as a Promising Indicator in Colorectal Cancer Prognosis: A Systematic Review

Abstract: The link between inflammation and cancer is still an attractive subject of many studies because systemic inflammatory response has been proven to play a pivotal role in cancer progression and metastasis. The strongest relationship between chronic inflammation and cancer development is observed in colorectal cancer (CRC). The evaluation of ratios derived from the routinely performed inflammatory biomarkers shows limited performances and limited clinical utility when individually used as prognostic factors for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 89 publications
0
23
0
Order By: Relevance
“…[ 11 ] Inflammation plays a role in tumor invasion, angiogenesis, cell proliferation, and immune cell suppression. [ 13 ] Various cells such as neutrophils, lymphocytes, monocytes, and platelets play a role in the systemic inflammatory process,[ 33 ] and many studies have reported quantification of these cells as outcome indicators in patients with tumors.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] Inflammation plays a role in tumor invasion, angiogenesis, cell proliferation, and immune cell suppression. [ 13 ] Various cells such as neutrophils, lymphocytes, monocytes, and platelets play a role in the systemic inflammatory process,[ 33 ] and many studies have reported quantification of these cells as outcome indicators in patients with tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the signi cant involvement of in ammation in tumor initiation and progression. Several recent studies have shown that systemic in ammatory response markers, including CRP 15 , glasgow prognostic score 16 , PLR 17 , LMR 18 , are associated with CRC and poor survival in many other cancers 19 . In particular, NLR, which is considered one of the markers of systemic in ammatory response, is closely related to the prognosis of patients with various types of cancer 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Of note, several composite inflammatory indicators, including but not limited to systemic immune-inflammation index (SII), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and lymphocyte-to-monocyte ratio (LMR), have been validated to be feasible in predicting the prognosis of various cancers and inflammatory diseases ( 16 19 ). These composite indicators, comprising biomarkers easily available in clinical settings such as peripheral lymphocytes, platelets, neutrophils, and monocytes, offer a comprehensive reflection of both local immune status and systemic inflammation condition ( 20 23 ). Whether these newly developed indicators presented equivalent predictive value in CKD has not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%